A brain gain with a brain drain - Oded Stark; Alexia Prskawetz; Christian Helmenstein (Institute for Advanced Studies (IHS), 1997)
We study human capital depletion and formation in an economy open to out-migration, as opposed to an economy which is closed. Under the natural assumption of asymmetric information, the enlarged opportunities and the associated different structure of incentives can give rise to a brain gain in conjunction with a brain drain. Migration by high-skill members of its workforce notwithstanding, the home country can end up with a higher average level of human capital per worker.
Keywords: F22; J24; J61; 330; - migration; brain drain; skill formation; asymmetric information